Sensitive and specific exonuclease III-assisted recombinase-aided amplification colorimetric assay for rapid detection of nucleic acids - Zhou, Y.; Zhang, J.; Sun, H.; Tao, D.; Xu, B.; Han, X.; Ren, R.; Ruan, J.; Steinaa, Lucilla; Hemmink, Johanneke D.; Han Jianlin; Li, X.; et al. (American Chemical Society, 2023)
The development of a contamination-free and on-site nucleic acid detection platform with high sensitivity and specificity but low-cost for the detection of pathogenic nucleic acids is critical for infectious disease diagnosis and surveillance. In this study, we combined the recombinase-aided amplification (RAA) with the exonuclease III (Exo III)-assisted signal amplification into a platform for sensitive and specific detection of nucleic acids of African swine fever virus (ASFV). We found that this platform enabled a naked eye visual detection of ASFV at a detection limit as low as 2 copies/μL in 30 min. As expected, no cross-reactivity was observed with other porcine viruses. In addition, to avoid aerosol contamination, a one-tube RAA-Exo III colorimetric assay was also established for the accurate detection of ASFV in clinical samples. Taken together, we developed a rapid, instrument-free, and low-cost Exo III-assisted RAA colorimetric-assay-based nucleic acid detection platform.